2021
DOI: 10.1021/acsanm.1c03106
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Control of Silver Nanoclusters by Tailoring Extra-Framework Cations in FAU-Y Zeolite: Implications for Tunable Emission

Abstract: Silver nanoclusters (Ag NCs) are emissive centers that are characteristic of high quantum yield, tunable emission, and large Stokes shift when confined inside zeolites, and their luminescence property is closely related to the cluster size, charge state, local environment, and extra activation. In this research, we evaluated the luminescence response of Ag NCs on the extra-framework cations by considering Na-type FAU-Y (NaY) as the parent zeolite. The extra-framework cations Na+ were partially substituted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Furthermore, the full width at half maximum (FWHM) of Ag CLs also showed Si/Al ratio dependency, which monotonously decreased with ascending desilicated degree or increased with ascending dealuminated degree. The red-shifted emission of Ag CLs and the reduced FWHM of the emission spectra with increasing desilicated degree indicate reduced energy splitting between the excited state and ground state of Ag CLs caused by decreased local crystal field and weaker coupling between the host lattice and luminescent center, which could be attributed to the expanded unit cell in the desilicated zeolites [ 19 , 44 ]. Similarly, the blue-shifted emission of Ag CLs and the increased FWHM of the emission spectra with increasing dealumination degree were due to increased local crystal field and stronger coupling between host lattice and luminescent center because of unit cell contraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the full width at half maximum (FWHM) of Ag CLs also showed Si/Al ratio dependency, which monotonously decreased with ascending desilicated degree or increased with ascending dealuminated degree. The red-shifted emission of Ag CLs and the reduced FWHM of the emission spectra with increasing desilicated degree indicate reduced energy splitting between the excited state and ground state of Ag CLs caused by decreased local crystal field and weaker coupling between the host lattice and luminescent center, which could be attributed to the expanded unit cell in the desilicated zeolites [ 19 , 44 ]. Similarly, the blue-shifted emission of Ag CLs and the increased FWHM of the emission spectra with increasing dealumination degree were due to increased local crystal field and stronger coupling between host lattice and luminescent center because of unit cell contraction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, framework modification through desilication or dealumination also manipulated the emission intensity of Ag CLs, as indicated by the integrated emission intensities in Figure 4 c. In order to study the influence of Ag chemical states on the luminescence properties of Ag CLs, the absorption spectra were measured and compared. As shown in Figure 5 a, the absorption band of NaY-Ag at 210 nm could be assigned to the 4d 10 →4d 9 5s 1 electronic transition of the separated Ag + in the zeolite framework, and the absorption band at approximately 270 nm originated from the postively charged Ag CLs, which was confined inside the FAUY zeolite [ 14 , 19 ]. According to the works from Chebbi and Azambre, the silver species that bear a positive charge have a shorter wavelength absorption than the neutral Ag n 0 clusters [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic units of the zeolite framework are constructed by connecting the corner-sharing TO 4 tetrahedra (T = Si, Al) of silicon–oxygen tetrahedra [SiO 4 ] 4– and aluminum–oxygen tetrahedra [AlO 4 ] 5– , often the Al 3+ can be substituted by P 3+ or Ga 3+ . Owing to the superior advantages of efficient ions exchange capacity that allows the easily intake of Ag + , uniform molecular-sized cage structure that benefits the confinement of functional clusters, and high chemical and thermal stability that enable long lasing applications, the zeolites have been considered as desirable hosts for Ag NCs. It has been reported that after thermal treatment, X-ray or electron beam irradiation on the Ag + -exchanged zeolites, Ag 2 + , Ag 3 n + , Ag 4 n + , and Ag 6 n + may be formed in the D6r or sodalite cages of zeolites. ,,, The formation efficiency and luminescence properties of Ag NCs can be manipulated through the selection of zeolite topological structure, framework, and extra-framework modifications, adjustment of silver loading degree, and thermal treatment. For example, recent studies indicated that the Ag NCs confined inside Linda A (LTA) and FAU zeolites exhibit blue-shifted emission when the radius of the extra-framework cation is reduced, and show significantly higher emission intensity in the Li + -type zeolites than in the Na + /K + /Ca 2+ -type zeolites; the peak emission wavelength of Ag NCs can be turned over 40 nm through desilication or dealumination treatment on the host FAU zeolites before Ag + -exchange; the Ag NCs in Li-LTA zeolites exhibit red-shifted emission from blue to green-yellow with increasing hydration level. , …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recent advances made in materials community highlight that zeolites can be promising host materials or starting materials for developing luminescent materials through the insertion of luminescent centers within the micropores of zeolites. 8,[10][11][12][13][14][15][16][17][18] Luminescent materials based on lanthanide doped zeolites (Ln-zeolite) has aroused great attention from researchers owing to the optical electronic configurations and unique optical behaviors of lanthanide ions alongside with the easy insertion of trivalent lanthanide (Ln 3+ ) ions within the micropores of zeolites via the ion-exchange procedure. 10,[19][20][21] Unfortunately, Ln 3+ -zeolite produces quite low luminescence output because of the weak absorption efficiency originating from the 'f-f parity forbidden transition' of Ln 3+ ions.…”
Section: Introductionmentioning
confidence: 99%